Colorimetric High-Throughput Screening Assay to Engineer Fungal Peroxygenases for the Degradation of Thermoset Composite Epoxy Resins - Dolz, Mikel; Mateljak, Ivan; Méndez-Sánchez, Daniel; Sánchez-Moreno, Israel; Gomez de Santos, Patricia; Viña-Gonzalez, Javier; Alcalde, Miguel (Frontiers in Catalysis, 2022)
At present, the end-of-life management of thermoset composite epoxy resins is limited to incineration and landfill storage, highlighting the demand for the development of more sustainable measures. Due to their broad spectrum of C-H oxyfunctionalization reactions, fungal unspecific peroxygenases (UPOs) are becoming important biotechnological tools in organic synthesis while their potential use in biodegradation processes should not be underestimated. Here, we present a colorimetric screening assay aimed at engineering UPOs for the degradation of epoxy resins. We based our study on Hexflow® RTM-6, a commercial epoxy resin used extensively in the aeronautics sector. UPO mutants from the short and long families were initially benchmarked by GC/MS to determine their potential N-dealkylation activity on N,N-bis(2-hydroxypropyl)-p-toluidine (NNBT), the main structural scaffold of Hexflow® RTM-6. A reliable high-throughput colorimetric screening method was developed to quantify the lactaldehyde released by UPO attack on the tertiary amine of NNBT. Based on an evolved UPO from Psathyrella aberdarensis that was expressed by yeast, a small subset of mutant libraries with different mutational loadings was constructed and screened for NNBT N-dealkylation, thereby establishing a directed evolution platform as a vehicle to engineer UPO composite degrading variants.